2021
DOI: 10.1051/e3sconf/202123203002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Tertiary Rice Panicle Branches

Abstract: Panicle branching trait of rice is one of the key factors in detemining grain yield. This study was aimed to elucidate the genetic inheritance pattern of the tertiary rice panicle branches trait. Six rice populations i.e F1, F1R, F2, F2R, BC1P1, and BC1P2 generation including parental lines were generated as materials. The experiment was conducted at IPB University, Bogor, Indonesia from April 2017 to February 2019. Several parameters of genetic inheritance was observed. The result revealed that the inheritanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…Additive gene effects can be exploited in early generations because the dominance effects are also non-significant and lower in magnitude than these additive effects. These findings agreed with those of Abebe, Alamerew & Tulu (2019) , Hastini et al (2021) and Lukman & Suyamto (2017) . In addition, additive × dominance type of gene interactions ( j ) were played a significant role in the inheritance of all the traits that were investigated, except the duration trait in (P 1 × P 2 ) and plant height in (P 3 × P 4 ) under water deficit conditions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additive gene effects can be exploited in early generations because the dominance effects are also non-significant and lower in magnitude than these additive effects. These findings agreed with those of Abebe, Alamerew & Tulu (2019) , Hastini et al (2021) and Lukman & Suyamto (2017) . In addition, additive × dominance type of gene interactions ( j ) were played a significant role in the inheritance of all the traits that were investigated, except the duration trait in (P 1 × P 2 ) and plant height in (P 3 × P 4 ) under water deficit conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Significant positive estimates of heterosis and heterobeltiosis among physiological and agronomic traits and its components in two studied crosses, which revealed the over-dominance plays an important role in inheritance of those traits. These findings were supported by several studies ( Ahmadikhah, 2018 ; Hossain et al, 2021 ; Kamara et al, 2017 ; Tiwari et al, 2019 ), wherein it has also been suggested that these aforementioned crosses could be used to explore the heterotic effects in hybrid rice breeding programs with water deficit conditions ( Concepcion et al, 2015 ; Guimarães, Stone & Silva, 2016 ; Hassan, 2017 ; Hastini et al, 2021 ; Potkile et al, 2018 ). Furthermore, significant heterosis percentages were recorded for these traits in studied crosses, which was corroborated by previous studies ( Gaballah et al, 2021 ; Ouyang, Li & Zhang, 2022 ; Sakran et al, 2022 ).…”
Section: Discussionsupporting
confidence: 53%
“…The increasing stem length found in this study appears to be due to plasticity in the level of stretching of the top of the stem, which affects the change in panicle length. Panicle length was positively correlated with the number of grains per panicle (Hastini et al., 2021; Jayaningsih et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Hastini et al. (2021) showed the genetic inheritance pattern of tertiary rice panicle branches using six rice populations and a complete design; the authors reported that the gene action of the number of tertiary branches and the number of grains on tertiary branches were additive and additive x additive. Farooq et al.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated the gene action of several rice characters. Hastini et al (2021) showed the genetic inheritance pattern of tertiary rice panicle branches using six rice populations and a complete design; the authors reported that the gene action of the number of tertiary branches and the number of grains on tertiary branches were additive and additive x additive. Farooq et al (2019) studied yield and yieldattributing characters and showed a high heritability associated with a high genetic improvement, indicating fixation of genes and presence of additive gene action.…”
mentioning
confidence: 99%